Patient-Derived Xenografts as a Model System for Radiation Research - Willey, Christopher D. (Semin Radiat Oncol, 2015)
The cancer literature is filled with promising preclinical studies demonstrating impressive efficacy for new therapeutics, yet translation of these approaches into clinical successes has been rare, indicating that current methods used to predict efficacy are sub-optimal. The most likely reason for the limitation of these studies is the disconnect between preclinical models and cancers treated in the clinic. Specifically, most preclinical models are poor representations of human disease. Immortalized cancer cell lines that dominate the cancer literature may be, in a sense, “paper tigers” that have been selected by decades of culture to be artificially driven by highly targetable proteins. Thus, although effective in treating these cell lines either in vitro or as artificial tumors transplanted from culture into experimental animals as xenografts, the identified therapies will likely underperform in a clinical setting. This inherent limitation not only applies to drug testing, but also to experiments with radiation therapy. Indeed, traditional radiobiology methods rely on monolayer culture systems, with emphasis on colony formation and DNA damage assessment that may have limited clinical translation. As such, there has been keen interest in developing tumor explant systems in which patient tumors are directly transplanted into, and solely maintained in vivo, using immunocompromised mice. These so-called Patient-Derived Xenografts (PDX) represent a robust model system that has been garnering support in academia and industry as a superior preclinical approach to drug testing. Likewise, PDX models have the potential to improve radiation research. In this review, we describe how PDX models are currently being used for both drug and radiation testing and how they can be incorporated into a translational research program.